Uniqueness of Layered Double Hydroxide Materials: A Critical Review of Synthesis Methods, Properties, Composites, and Remediation Mechanism - Normah, Normah; Oktriyanti, Melantina; Adhiyanti, Nurmalina; Sajidah, Happy Bunga Nasyirahul (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Layered Double Hydroxides (LDHs) are a class of anionic clays known for their tunable structure, high surface area, and versatile ion exchange capabilities, making them highly attractive for environmental remediation. This critical review explores the uniqueness of LDH materials by examining recent advancements in their synthesis methods, structural and physicochemical properties, and the development of LDH-based composites. Various synthesis approaches including co-precipitation, hydrothermal, and mechanochemical methods are evaluated in relation to their influence on LDH morphology, stability, and functionality. The review also highlights the integration of LDHs with other materials such as metal oxides, carbon-based supports, and metal organic frameworks (MOFs), which enhance their photocatalytic and adsorptive performances. Special attention is given to the mechanisms underlying pollutant removal, including ion exchange, surface complexation, and photocatalytic degradation. Comparative analysis of different modifications reveals trends in application performance and identifies current challenges that must be addressed to optimize LDHs for large-scale and multi-functional environmental applications. This review provides critical insight into the future potential of LDH materials as sustainable and efficient solutions for water and wastewater treatment.